Furanyl-Rhodanines Are Unattractive Drug Candidates for Development as Inhibitors of Bacterial RNA Polymerase - Mariner, Katherine R. (American Society for Microbiology (ASM), 2010)
Previous studies suggest that furanyl-rhodanines might specifically inhibit bacterial RNA polymerase (RNAP). We further explored three compounds from this class. Although they inhibited RNAP, each compound also inhibited malate dehydrogenase and chymotrypsin. Using biosensors responsive to inhibition of macromolecular synthesis and membrane damaging assays, we concluded that in bacteria, one compound inhibited DNA synthesis and another caused membrane damage. The third rhodanine lacked antibacterial activity. We consider furanyl-rhodanines to be unattractive RNAP inhibitor drug candidates.